Disease Severity and Genotype Affect Physical Growth in Children With Familial Mediterranean Fever - Rabia Miray KIŞLA EKİNCİ,; Sibel BALCI,; Eray AKAY,; Dilek DOĞRUEL,; Derya Ufuk ALTINTAS,; Mustafa YILMAZ, (Archives of Rheumatology, 2019)
Objectives: This study aims to analyze the growth parameters in children with familial Mediterranean fever (FMF) according to disease characteristics including genotype and disease severity by a recently validated tool in relatively more patients. Patients and methods: This retrospective study included 126 patients with FMF (70 males, 56 females; mean age 7.3±3.6 years; range, 4.1 to 18 years). MEditerranean FeVer (MEFV) gene analysis was performed with a molecular diagnostics tool by using a next-generation sequencing platform. Disease severity was determined for the first visit by the validated tool in children, international severity scoring system for FMF. Growth parameters including weight and height were investigated after standard deviation (SD) scores were calculated by anthropometric references in Turkish children. Results: Median follow-up duration was 74.7 months (range, 7.5 to 169 months). Ninety-three patients (73.8%) had at least one M694V mutation in MEFV gene. Six patients (4.8%) had severe disease, 58 (46%) had intermediate severity, and 62 (49.2%) had mild disease. Mean height SD score was significantly lower at last visit than before colchicine treatment. Initial and last height and weight SD scores were lower in patients with at least one M694V mutation than those without. However, the difference was statistically significant for only initial height SD score. We also found statistically significant lower initial height, final height, and weight SD scores in patients with intermediate severity-severe disease activity than mild disease. Conclusion: We advise physicians to score disease severity prospectively and pay attention to patients with intermediate severity-severe disease to avoid growth disturbances.